2015 IEEE Electric Ship Technologies Symposium (ESTS) 2015
DOI: 10.1109/ests.2015.7157882
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the development of a battery-based pulsed power system

Abstract: The development of compact, portable pulsedpower devices is of continuing interest, and recent technological developments such as high-energy-density capacitors, the emergence of SiC high-power devices, and the combined high power and energy density in electrochemical energy storage devices present an opportunity to use these technologies in applications of interest, such as high power lasers, railguns, and microwave systems. Several challenges exist when attempting to integrate these emerging devices into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…observed that most solutions use various types of transformer-based DC-DC converters [15][16][17][18][19][20][21][22]. In [15][16][17], a single active bridge was applied, while in some other works, a resonant converter can be found [19][20][21][22].…”
Section: The Setup Of the Marx Generatormentioning
confidence: 99%
See 2 more Smart Citations
“…observed that most solutions use various types of transformer-based DC-DC converters [15][16][17][18][19][20][21][22]. In [15][16][17], a single active bridge was applied, while in some other works, a resonant converter can be found [19][20][21][22].…”
Section: The Setup Of the Marx Generatormentioning
confidence: 99%
“…Taking into account these requirements, a portable DC power supply has been developed on the basis of silicon carbide (SiC) power device technology. The first step of the research was a literature review in the area of high-voltage power supplies and it was observed that most solutions use various types of transformer-based DC-DC converters [15][16][17][18][19][20][21][22]. In [15][16][17], a single active bridge was applied, while in some other works, a resonant converter can be found [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…M/S Viking Queen will soon be retrofitted with batteries [6], while M/S Ampere is in operation and is driven by batteries only [7]. Using batteries on naval vessels to take care of pulse loads from the weapons system has been suggested [8], [9]. Batteries can also be used for emergency power, as demonstrated in [10].…”
Section: Introductionmentioning
confidence: 99%